In situ abundance and carbon fixation activity of distinct anoxygenic phototrophs in the stratified seawater lake Rogoznica - Pjevac, Petra; Dyksma, Stefan; Goldhammer, Tobias; Mujakić, Izabela; Koblížek, Michal; Mußmann, Marc; Amann, Rudolf; Orlić, Sandi (Environmental microbiology, 2019)
Summary Sulphide‐driven anoxygenic photosynthesis is an ancient microbial metabolism that contributes significantly to inorganic carbon fixation in stratified, sulphidic water bodies. Methods commonly applied to quantify inorganic carbon fixation by anoxygenic phototrophs, however, cannot resolve the contributions of distinct microbial populations to the overall process. We implemented a straightforward workflow, consisting of radioisotope labelling and flow cytometric cell sorting based on the distinct autofluorescence of bacterial photopigments, to discriminate and quantify contributions of co‐occurring anoxygenic phototrophic populations to in situ inorganic carbon fixation in environmental samples. This allowed us to assign 89.3% ± 7.6% of daytime inorganic carbon fixation by anoxygenic phototrophs in Lake Rogoznica (Croatia) to an abundant chemocline‐dwelling population of green sulphur bacteria (dominated by Chlorobium phaeobacteroides), whereas the co‐occurring purple sulphur bacteria (Halochromatium sp.) contributed only 1.8% ± 1.4%. Furthermore, we obtained two metagenome assembled genomes of green sulphur bacteria and one of a purple sulphur bacterium which provides the first genomic insights into the genus Halochromatium, confirming its high metabolic flexibility and physiological potential for mixo‐ and heterotrophic growth.